Namibia : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Namibia was negatively impacted by the 2008 global financial crisis, reversing years of strong economic performance and deteriorating both fiscal and external positions. Accordingly, the authorities have committed to undertake fiscal consolidation with a view to reduce the fiscal deficit to 2.6 percent of GDP by 2014. IMF staff emphasized the need for an earlier withdrawal of stimulus measures and ambitious fiscal consolidation. Staff also called for streamlining fiscal rules with the debt-to-GDP ratio to help isolate fiscal policy from volatile Southern Africa Customs Union (SACU) revenues.